2015
DOI: 10.1007/s13555-015-0079-0
|View full text |Cite
|
Sign up to set email alerts
|

Eruptive Tumors of the Follicular Infundibulum: An Unexpected Diagnosis of Hypopigmented Macules

Abstract: BackgroundTumor of the follicular infundibulum (TFI) is considered as a rare benign neoplasm providing two distinctive clinical patterns: the solitary and the eruptive form. The clinical presentations resemble many other dermatologic conditions and require histopathological study to make a definite diagnosis.ObjectiveTo inform physicians of a clinical presentation of TFI.Case ReportWe report on a 50-year-old man who presented with multiple asymptomatic hypopigmented macules resistant to the treatments. The his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
0
5
0
3
Order By: Relevance
“…These lesions may occur in younger patients and can assume a variety of clinical manifestations including multiple hypopigmented macules, papules, or atrophic plaques with irregular or angulated borders. 1 , 2 Similar to their solitary counterparts, multiple TFI almost always cluster on the head and neck region. However, recently Haddad et al 5 reported a case in which TFI not only involved the head and neck but also the posterior calves.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…These lesions may occur in younger patients and can assume a variety of clinical manifestations including multiple hypopigmented macules, papules, or atrophic plaques with irregular or angulated borders. 1 , 2 Similar to their solitary counterparts, multiple TFI almost always cluster on the head and neck region. However, recently Haddad et al 5 reported a case in which TFI not only involved the head and neck but also the posterior calves.…”
Section: Discussionmentioning
confidence: 89%
“…An eruptive variant, known as infundibulomatosis , has been described and may present as multiple hypopigmented macules or papules, with irregular borders. 1 , 2 In addition, TFI may be associated with other cutaneous neoplasms, such as basal cell carcinoma, nevus sebaceous, and trichilemmoma, among others, 3 and with Cowden syndrome. 4 More recently, an atypical clinical variant involving the face and posterior calves was described in the Brazilian literature.…”
Section: Introductionmentioning
confidence: 99%
“…24 Multiple eruptive lesions of TFI, also called infundibulomas, 4,5 account for around 7% of cases. 12 They tend to affect the head/neck and trunk and then typically present as small, well defined hypopigmented papules or more frequently macules as shown in figures of several previous publications, [4][5][6][7][8][9][10][11][12][13][14][15][16][18][19][20][21] simulating seborrheic ker-atosis, type stucco keratosis. Clinical images from Kossard et al 4 are presented as an excellent representative example of such cases (Figure 9).…”
Section: Discussionmentioning
confidence: 99%
“…It comprises the infundibulum, isthmus, bulge, stem, and bulb 26 . As part of its morphological alterations TFI has been described as a neoplastic process isolated and multiple, 1–22 but also as a secondary, reactive phenomenon. Thus, originally considered to represent a distinctive epithelial neoplasm, subsequent publications noted TFI features in the vicinity of other lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation